MALAYSIA TEACHER EDUCATION - bin Kamin, Yusri (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
The education system in Malaysia is centralized and top-down Overseen by the Ministry of Education (MoE). Each state and federal territory has an Education Department to co-ordinate educational matters. The main legislation governing education is the Education Act of 1996. The Malaysian government provides free education for primary and secondary level11 years for each student